Mixed‐matrix membranes incorporating hierarchical ZIF‐8 towards enhanced CO2/N2 separation - Ting Xia; Yuyang Wu; Taotao Ji; Wenjing Hu; Kunpeng Yu; Xinyu He; Ben Hang Yin; Yi Liu (Smart Molecules)
Abstract Metal‐organic framework (MOF) has been widely used as filler of mixed‐matrix membranes (MMMs) because of their tunable pore sizes, large surface areas, and rich functional groups. However, a relatively high diffusion barrier in the framework of bulk MOF fillers inevitably reduces gas permeability. Introduction of hierarchically porous structure represents an effective method for reducing guest diffusion resistance with no compromise in gas selectivity. In this study, hierarchical ZIF‐8 (H‐ZIF‐8) was prepared using carboxylated polystyrene (PS‐COOH) nanospheres as a hard template. Owing to the introduction of carboxyl groups, electrostatic interaction between PS nanospheres and Zn2+ ions is enhanced, facilitating uniform embedment of PS nanospheres in bulk ZIF‐8 filler. After dissolution of PS‐COOH nanospheres with dimethylformamide solvents, H‐ZIF‐8 with tunable textural properties is readily obtained. Gas permeation results indicate that compared with bulk ZIF‐8 filler, fast diffusion pathways for guest molecules are established in H‐ZIF‐8 filler, resulting in a CO2/N2 separation factor (SF) of 48.77 with CO2 permeability of 645.76 Barrer in terms of H‐ZIF‐8 MMMs with 6 wt % loading, which well exceeds the 2008 Robenson upper bound for CO2/N2 gas pair, thus showing promising prospects for high‐efficiency CO2 capture from flue gas.